EXPERIENCES OF PROFESSIONAL NURSES USING COMPUTER TECHNOLOGY IN THE INTENSIVE CARE UNIT SETTING IN SWAZILAND. - Sibandze, Bongani T.; Mallinson, Kevin R. (Africa Journal of Nursing & Midwifery, 2017)
The use of computer technology by nurses in the intensive care unit (ICU) setting is relatively new in Swaziland. In 2010, the second ICU opened in the country and very few nurses had been trained in critical care nursing. Understanding the nurses' experiences with computer technology use in the ICUs in Swaziland may reveal effective strategies for the adoption and optimisation of the new technology for patient care activities. The purpose of this qualitative study was to explore the experiences of professional nurses using computer technology in the ICU setting in the Swazi context. Purposive sampling of ICU nurses (N = 13) was done at two hospitals in Swaziland to engage in individual face-to-face interviews. Colaizzi's method guided the thematic analysis of the narrative data. Two themes emerged from the data analysis: practice value benefits and computer utilisation challenges. The narrative data revealed that the nurses valued the technology, but experienced challenges when using computers to perform their daily nursing activities. Nurses perceived that computers made work easier and contributed to quality improvement and resource utilisation. However, the challenges included a lack of institutional support and resource supplies, insufficient orientation and training and unreliable computer systems and Internet connectivity. As the use of computers by ICU nurses becomes the standard in Swaziland, these findings suggest that a well-designed orientation and ongoing institutional support may serve to optimise the use of the technology. Further research may explore the impact of computer technology on work-related quality of life for nurses and its effectiveness in improving patient care and clinical outcomes.